Kemampuan Menentukan Unsur Intrinsik Cerpen Bintang di Gubuk Karya Yohanes E. L. Ofong dalam Kumpulan Cerpen “Wajah Indonesiaku” Pada Siswa Kelas VII SMP Negeri Ine Pare Tahun Ajaran 2020/2021 - Serlin, Maria Floriana; Jamaludin, Zaenab (Retorika: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2021)
This study aims to determine and describe the ability of grade VII students of SMP Negeri Ine Pare for the 2020/2021 academic year in determining the intrinsic elements of Bintang di Gubuk short story by Yohanes E. L. Ofong. The approach used in this study is a quantitative approach because the data obtained using numbers. The data collection method used to obtain data in this study is the test method. In this study, researchers used essay tests to determine the ability of student learning outcomes. The theory used is literary theory and learning outcomes evaluation theory. The results of this study indicate that the seventh grade students of SMPN Ine Pare for the academic year 2020/2021 are able to determine the intrinsic elements of "Bintang di Gubuk" short story by Yohanes E.L Ofong. It is said like that because the results of data analysis show that the students' abilities reached 85.29% of the 29 students. Meanwhile, 5 people who did not complete it with a presentation of 14.70%.